Standardization of conditions for extraction of flavonoids from glycyrrhiza glabra callus cultures - U.VIJAYALAKSHMI,; ABHILASHA SHOURIE, (International Journal of Pharma and Bio Sciences, 2017)
Glycyrrhiza glabra is a perennial herb of Fabaceae family containing wide range of biologically active substances including flavonoids. The medicinal properties of the plant are mainly attributed to the presence of flavonoids. Extraction is an important step in isolation of these flavonoids, as it is a crucial process requiring intense standardization. The aim of the current research was to determine the optimized conditions for efficient and simultaneous extraction of major flavonoids from Glycyrrhiza glabra callus. Callus extracts were prepared with ethanol using Heat stirred extraction (HSE) method. Optimization was done by using L16 orthogonal design of experiment. The effect of factors such as Temperature, extraction time, solvent concentration material ratio, number of extractions on content of flavonoids was investigated. The maximum flavonoid content (10.2 mg/g) was obtained under optimum conditions of 1:30 material ratio, using 70% ethanol as solvent for 4 hrs extraction duration at temperature 85 ºC in three cycles of extractions. Ethanol concentration and extraction time were found to be the most significant factors influencing the flavonoid yield, and had a positive effect on flavonoid contents.